Mortality from plastic ingestion and net entanglement in marine birds - description of three cases - Garcês Andreia; Soeiro Vanessa; Loio Sara; Pires Isabel (Veterinarski Glasnik)
Plastic debris is a significant threat to marine ecosystems, notably affecting seabird populations globally. In this report, the authors document deaths related to plastic ingestion in a Northern Gannet (Morus bassanus, Linnaeus, 1758) and net entanglement in a Yellow-Legged Gull (Larus michahellis, Naumann, 1840) and a Northern Gannet (M. bassanus, Linnaeus, 1758) in Northern Portugal. All three animals died as a result of either plastic entanglement or ingestion. While this report highlights just three cases, it emphasizes the severe negative impacts of plastic on seabirds, ultimately leading to the deaths of these animals.